THE MID-PLEISTOCENE CLIMATE TRANSITION: ONSET OF 100 KA CYCLE LAGS ICE VOLUME BUILD-UP BY 280 KA - Mudelsee M.; Schulz M. (My University, 1997)
The Mid-Pleistocene Climate Transition (MPT) is the complex climatic change which brought the Late Pleistocene ice ages. We explore the MPT in the time and frequency domains by new methods of time series analysis. High-resolution oxygen isotope records reveal that the ice volume-related increase in δ18O mean (amplitude: 0.29 ± 0.05 (1 − σμ) ‰, transition midpoint: 922 ± 12 ka, duration: 40 ± 9 ka) significantly preceded the abrupt increase in the amplitude of the ~ 100 ka cycle at 641 ± 9 ka. This finding can be quantitatively simulated using a simple ice-bedrock model in which, due to the additional ice, the calving threshold is exceeded. The simulated calving events prior to ~ 650 ka are separated by ~ 77 ka, whereas after ~ 650 ka they occur pseudo-periodically with a mean period of nearly 100 ka. The cause for the delay of the ~ 100 ka calving cycle was not a slow bedrock relaxation; rather, the coincidental combination of insolation, existing ice mass, and bedrock depression.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен